Introductory Note to the Special Issue: Teaching as an Intergenerational Profession: How Generational Diversity Contributes to Teacher Education and Professional Development (Revista Lusófona de Educação, 2026)
Introduction to the thematic dossier:Teaching as an Intergenerational Profession: How Generational Diversity Contributes to Teacher Education and Professional Development